Evaluating narrative exposure therapy for post‐traumatic stress disorder and depression symptoms: A meta‐analysis of the evidence base. (15th July 2020) - Raghuraman, Shruti; Stuttard, Nathan; Hunt, Nigel
Abstract : Narrative exposure therapy (NET) is an intervention for trauma spectrum disorders. Originally developed to treat refugee populations, NET has since been tested for efficacy across different settings. In this review, the NET evidence base is examined through a retrieval, synthesis and appraisal of randomized controlled trials (RCTs) published since 2002. Two independent reviewers (S. R. and N. S.) searched online databases including EMBASE, PsycINFO and PubMed. Twenty‐four RCTs were selected for a meta‐analysis of three outcomes: post‐traumatic stress disorder (PTSD) diagnosis and PTSD and depression symptoms. All outcomes were analysed at short‐term (3–4 months), midterm (6–7 months) and long‐term (≥12 months) data points. A random‐effects model was applied to yield standardized mean differences (SMDs) and odds ratios (ORs) as indicators of NET treatment effect. Subgroup analyses for type of trauma and type of control groups were conducted to examine potential heterogeneity. For the NET group, moderate effect sizes for PTSD symptom severity were observed at midterm and long term and at midterm for depression symptom severity. The number of PTSD diagnoses decreased significantly in the short term for the NET condition, but this was not sustained at the long term. Caution must be exercised when interpreting these results due to high heterogeneity estimates and low quality of evidence across trials. Potential small‐study effects further complicate the interpretation of the findings. Recommendations are made for augmenting statistical significance research with qualitative analyses of NET efficacy to better inform clinical practice.